Inovasi Pemanfaatan Media Video Karikatur Menggunakan Bahasa Manggarai Untuk Meningkatkan Pengetahuan Ibu Hamil Tentang Persiapan Fisik Dan Psikis Dalam Persiapan Persalinan - Minda, Agustina Vinensia; Hastuti, Agnes Sri; Suriati, Flaviana Atri; Ndae, Astuti; Rembong, Felisitas Urbana; Dese, Elisabet; Manggul, Makrina Sedista (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Preparing for childbirth is a vital component of the overall childbirth process, aimed at promoting optimal health prior to delivery. One significant factor contributing to maternal mortality rates (MMR) is the lack of readiness among mothers to face childbirth. In response to this issue, numerous initiatives have been undertaken to reduce MMR, including providing physical and psychological support throughout the pregnancy. Community service efforts have identified several challenges faced by pregnant women, particularly concerning their readiness for childbirth, which encompasses physical, mental, and emotional preparation. This initiative employs educational strategies, utilizing counseling sessions and cartoon videos in the Manggarai language to facilitate understanding. The primary goal of this activity is to educate pregnant women on both physical and psychological preparations, thereby enhancing their knowledge and confidence as they approach childbirth. The curriculum focuses on essential aspects of preparing for childbirth, addressing both physical and mental readiness. The initiative successfully implements educational sessions accompanied by engaging cartoon videos, which pregnant women can view directly. As a result, there has been a notable improvement in their understanding of what is necessary for childbirth preparation, encompassing both physical and psychological dimensions. The provision of education concerning the physical and psychological aspects of childbirth preparation has significantly increased pregnant women's knowledge, fostering a positive attitude and greater confidence as they approach the impending birth of their child.ABSTRAKPersiapan persalinan memiliki peranan penting dalam proses kelahiran, dengan tujuan utama meningkatkan kesehatan ibu secara optimal sebelum melahirkan. Ketidaksiapan ibu menghadapi persalinan dapat menjadi salah satu faktor penyebab tingginya angka kematian ibu (AKI). Berbagai upaya telah dilakukan untuk menurunkan AKI, termasuk dengan mempersiapkan secara fisik dan psikis selama masa kehamilan. Program pengabdian masyarakat menunjukkan adanya beberapa permasalahan, khususnya yang berkaitan dengan ibu hamil, di antaranya adalah kurangnya persiapan persalinan yang mencakup kesiapan fisik, mental, dan emosional serta dukungan saat persalinan. Metode yang diterapkan dalam kegiatan ini adalah edukasi melalui penyuluhan dan penyampaian informasi menggunakan video karikatur berbahasa Manggarai. Kegiatan ini bertujuan untuk memberikan edukasi kepada ibu hamil mengenai persiapan fisik, mental, dan psikis, agar mereka memiliki pengetahuan yang lebih baik dalam menghadapi proses persalinan. Materi yang diberikan mencakup persiapan fisik dan psikis menjelang kelahiran. Kegiatan ini berhasil dilaksanakan dengan adanya penyampaian edukasi serta pemutaran video karikatur yang ditonton langsung oleh ibu hamil. Terdapat peningkatan pengetahuan ibu mengenai persiapan persalinan, baik secara fisik maupun psikis. Melalui edukasi tentang persiapan fisik dan psikis bagi ibu hamil, terjadi peningkatan pengetahuan yang signifikan. Hal ini mendorong terbentuknya sikap positif dari ibu hamil dalam mempersiapkan proses persalinan mereka.